FORMATION OF PEDAGOGICAL SKILLS OF HIGHER SCHOOL TEACHERS - Nina B. Dremova; Aleksandr I. Konoplya (Высшее образование в России)
The article presents the experience of Kursk State Medical University on the formation of pedagogical skills of teachers, covers the main directions of the work of the Faculty for Qualification Improvement and university departments. Due to the activities of 13 pedagogical schools at KSMU the lectures can raise their professional competences and master their pedagogical skills on the basis of innovative educational models, new pedagogical technologies, author’s programs, and a special training “Formation and devekopment of teaching mastery”.